ACTUAL PROBLEMS OF ACADEMIC WRITING - Оразбаева, Фаузия (Pedagogy and Psychology, 2022)
Academic writing is aimed at regulating the scientific form of written language communication. When mastering academic writing, the knowledge of communicants strives to achieve new scientific indicators. Academic writing is a type of text communication that directs students to an independent search, determining the content and structure of scientific work. Academic writing develops the scientific creative abilities of the applicant as a fragment of text communication and a certain type of text formation. The methodological basis of academic writing is formed by the integration methods of linguistics, functional stylistics, psychology, cognitive linguistics, text linguistics and other scientific fields. These methods implement the author-addressee relationship in a complex. The consideration of the academic text in the discourse determines the goal of the communicants. The formation of academic writing competencies directs the applicant to new searches. Writing at the level of a scientific text forms communicative, discursive competence. Working with text opens up wide opportunities for the formation of students’ communication skills, improving language skills and abilities.